Woman’s Body as the Site of Violence in Parijat’s Blue Mimosa - Mishra, Indira Acharya (Researcher: A Research Journal of Culture and Society, 2020)
The article aims to analyze Parijat's Blue Mimosa, which was originally published as Śirīṣako Phūla (1965) from the feminist perspective. Feminists argue that patriarchy is unfriendly to women. They explain that because of biased patriarchal gender roles women suffer from gender-based violence. They claim that in patriarchy men have special power and privileges which allow them to dominate and control women to their benefit. They use corporal punishment and sexual violence in case women deny to submit to them. Thus, feminists protest the imposition of traditional gender roles in the process of socialization. They demand for a more egalitarian perspective towards gender which allows human individuals to live according to their interests and capacities. In Blue Mimosa, the female characters become the victim of gender-based violence. They are physically assaulted, raped, and murdered. Their bodies become the site where men enact violence. Thus, feminism is relevant to analyze the text. The article argues that these female characters become the victim of violence just because they are women. The article helps to understand how women suffer from gender-based violence in patriarchy.